2011
DOI: 10.1097/rhu.0b013e31822be4e8
|View full text |Cite
|
Sign up to set email alerts
|

Capillaroscopic Pattern at the Toes of Systemic Sclerosis Patients

Abstract: Capillaroscopy of the toes of SSc also shows patterns characteristic of SSc. However, these patterns differ from the respective patterns of the fingers, which is probably related to less-severe RP and lower skin score at the feet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 8 publications
(4 reference statements)
1
23
0
1
Order By: Relevance
“…However, concerns about the reproducibility of thermography have limited its use (4). As RP affects both hands and feet (5, 6) we used infrared thermography to measure skin temperature differences between the palm of the hand and the fingers and between the dorsum of the feet and the toes in patients with RP and normal healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…However, concerns about the reproducibility of thermography have limited its use (4). As RP affects both hands and feet (5, 6) we used infrared thermography to measure skin temperature differences between the palm of the hand and the fingers and between the dorsum of the feet and the toes in patients with RP and normal healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the strong diagnostic potential of nailfold capillaroscopy in SSc, we have previously studied nailfold capillaroscopic changes of the toes in a group of 36 SSc patients. Interestingly, whereas in the fingers, a “scleroderma” type capillaroscopic pattern has been found in 97.2% (35/36) of patients, in the toes, it has been detected in only 66.7% (24/36) of cases ( P < .05) . On the one hand this observation confirms the generalized nature of microangiopathy in SSc; on the other hand, the significantly lower frequency of the “scleroderma” type capillaroscopic pattern of the toes indicates the diversity of the capillaroscopic findings in different nailfold areas.…”
Section: Introductionmentioning
confidence: 72%
“…Here a distinct discrepancy to other study results is seen. Lambova et al examined the toes of 36 patients with SSc and found megacapillaries in 11 patients, hemorrhages in 3 and avascular areas in 15. The reason for this discrepancy might be the different patient collectives.…”
Section: Discussionmentioning
confidence: 99%